Effect of Tillage System and Organic Matter Management Interactions on Soil Chemical Properties and Biological Activity in a Spring Wheat Short-Time Cultivation - Barbara Breza-Boruta; Karol Kotwica; Justyna Bauza-Kaszewska (Energies, 2021)
Properly selected tillage methods and management of the available organic matter resources are considered important measures to enable farming in accordance with the principles of sustainable agriculture. Depending on the depth and intensity of cultivation, tillage practices affect soil chemical composition, structure and biological activity. The three-year experiment was performed on the soil under spring wheat (cv. Tybalt) short-time cultivation. The influence of different tillage systems and stubble management on the soil’s chemical and biological parameters was analyzed. Organic carbon content (OC); content of biologically available phosphorus (Pa), potassium (Ka), and magnesium (Mg); content of total nitrogen (TN), mineral nitrogen forms: N-NO3 and N-NH4 were determined in various soil samples. Moreover, the total number of microorganisms (TNM), bacteria (B), actinobacteria (A), fungi (F); soil respiratory activity (SR); and pH in 1 M KCl (pH) were also investigated. The results show that organic matter amendment is of greater influence on soil characteristics than the tillage system applied. Manure application, as well as leaving the straw in the field, resulted in higher amounts of organic carbon and biologically available potassium. A significant increase in the number of soil microorganisms was also observed in soil samples from the experimental plots including this procedure.